DAILY PROFILE OF BLOOD PRESSURE AND STATE OF COGNITIVE FUNCTION IN PATIENTS WITH ARTERIAL HYPERTENSION - Dotsenko, M.Ya.; Herasymenko, L.V.; Shekhunova, I.O.; Molodan, O.V.; Malynovska, O.Ya.; Skorokhodova, N.O.; Yatsenko, O.V. (World of Medicine and Biology, 2021)
The article is devoted to the problem of arterial hypertension as the most important risk factor for the development of cognitive impairment. In 39 and 32 patients with arterial hypertension with cognitive dysfunctions, a significant impairment of the arterial pressure daily profile by systolic and diastolic blood pressure was found, against 19 and 16 of patients with similar indices in the group without cognitive impairment. With the decrease of the MoCA-test scores, there were correlations of the daily index of systolic and diastolic blood pressure and, as well as indices of systolic blood pressure variability per day and night. We have found that patients with hypertonic disease of stage II with the presence of cognitive impairment are characterized by a significant prevalence of the pathological types of arterial pressure daily profile.“Non-dipper” and “Night-peaker” (46.2 % and 19.2 %, respectively).
Keywords: hypertonic disease; blood pressure monitoring; cognitive impairment